META-ANALYSIS STUDY: IMPLEMENTATION OF DIFFERENTIATED LEARNING IN IMPROVING ELEMENTARY SCHOOL STUDENTS' LEARNING OUTCOMES - Rona Taula; Syofiani; Yulfianora; Ira Rahmani Jusar; Adek Sri Rahayu; Amanda Mardiana Putri; Novita Sari (Jurnal Cakrawala Pendas, 2026)
Differentiated instruction is a learner-centered approach that accommodates students' diverse readiness levels, interests, and learning profiles. Although it has been widely implemented across various educational settings, previous studies have reported inconsistent findings regarding its effectiveness in improving elementary school students' learning outcomes. Therefore, this study aimed to examine the effectiveness of differentiated instruction on elementary school students' learning outcomes through a meta-analysis. The study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 15 eligible studies involving 200 participants were included in the analysis. Data were analyzed using JASP version 0.18 under the random-effects model. Heterogeneity was assessed using Cochran's Q test, while publication bias was evaluated through funnel plot analysis, Egger's regression test, and Rosenthal's Fail-Safe N. The results revealed that differentiated instruction had a statistically significant and large positive effect on elementary school students' learning outcomes, with a pooled effect size of 1.561 (SE = 0.206; 95% CI = 1.157–1.966; Z = 7.576; p < .001). The heterogeneity analysis indicated significant variability among the included studies (Q = 270.720, p < .001), supporting the use of the random-effects model. Furthermore, the publication bias analyses demonstrated that the pooled effect estimate was stable and was not substantially influenced by publication bias, as indicated by the funnel plot, Egger's regression test, and Rosenthal's Fail-Safe N. In conclusion, differentiated instruction is an effective instructional approach for improving elementary school students' learning outcomes and is recommended as an adaptive, inclusive, and student-centered teaching strategy.